2010
DOI: 10.1128/jb.00512-10
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Genome of Methylobacillus flagellatus as Defined through Comprehensive Proteomics and New Insights into Methylotrophy

Abstract: In recent years, techniques have been developed and perfected for high-throughput identification of proteins and their accurate partial sequencing by shotgun nano-liquid chromatography-tandem mass spectrometry (nano-LC-MS/MS), making it feasible to assess global protein expression profiles in organisms with sequenced genomes. We implemented comprehensive proteomics to assess the expressed portion of the genome of Methylobacillus flagellatus during methylotrophic growth. We detected a total of 1,671 proteins (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Such highly expressed genes may correspond to proteins that are difficult to detect directly using mass spectrometry due to poor extraction efficiencies and/or small numbers of tryptic fragments. Indeed, many of these genes are predicted to encode small or transmembrane proteins that are known to have lower levels of detectability with the shotgun proteomics approach (13). Alternatively, some of the genes for proteins annotated as hypothetical proteins (with no homology to known proteins) may encode small RNA molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such highly expressed genes may correspond to proteins that are difficult to detect directly using mass spectrometry due to poor extraction efficiencies and/or small numbers of tryptic fragments. Indeed, many of these genes are predicted to encode small or transmembrane proteins that are known to have lower levels of detectability with the shotgun proteomics approach (13). Alternatively, some of the genes for proteins annotated as hypothetical proteins (with no homology to known proteins) may encode small RNA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…A high level of expression of XoxF proteins in M. mobilis JLW8 provides additional evidence for a role in methanol oxidation in this organism. Other highly abundant oxidoreductases included a NAD-dependent aldehyde dehydrogenase of unknown specificity (Mmol_0791), similarly abundant in a related species, Methylobacillus flagellatus KT, previously investigated using shotgun proteomics (13), and a NADH:flavin oxidoreductase (Mmol_0733) that also has unknown substrate specificity. The former was more abundant on methanol, while the latter was present at similar levels on both substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation suggested that stearyl alcohol induces expression of many extracellular proteins and prompted us to investigate the multiple aspects of NT80 cells' response to stearyl alcohol. Several previous studies reported the effects of methanol and ethanol on bacterial cells (Hendrickson et al, 2010;Lu et al, 2012) and several other studies examined the mechanism of assimilation of n-alkanes by bacteria (Bouchez Naïtali et al, 1999;Tani et al, 2001;Throne-Holst et al, 2006). The effects of fatty alcohols on bacterial cells, however, have hardly been explored.…”
Section: Introductionmentioning
confidence: 98%